Wheat Rhizosphere Microbiota Respond to Changes in Plant Genotype, Chemical Inputs, and Plant Phenotypic Plasticity - Jacquiod, Samuel; Raynaud, Tiffany; Pimet, Eric; Ducourtieux, Chantal; Casieri, Leonardo; Wipf, Daniel; Blouin, Manuel (Frontiers in Ecology and Evolution, 2022)
Because modern wheat varieties selected since the Green Revolution are generally grown with synthetic chemical inputs, and ancient varieties released before 1960 without, it remains unclear if changes observed in rhizosphere microbiota are due to (i) changes in wheat genotypes via breeding, (ii) modifications of the environment via synthetic chemical inputs, or (iii) phenotypic plasticity, the interaction between wheat genotype and the environment. Using a crossed factorial design in the field, we evaluated the effects of either modern or ancient wheat varieties grown with or without chemical inputs (a N-fertilizer, a fungicide and an herbicide) on “microbiome as a phenotype”. We analysed the rhizosphere microbiota via bacterial and fungal amplicon sequencing, coupled to microscope observations of mycorrhizal associations. We found that plant genotype and phenotypic plasticity had the most influence on the rhizosphere microbiota, whereas inputs had only marginal effects. The phenotypic plasticity was particularly important in explaining diversity variations in bacteria and fungi, but had no impact on the mycorrhizal association. Our results show the interest to consider the interaction between wheat genotype and the environment in breeding programs, by focusing on genes involved in the phenotypic plasticity of plant-microbe interactions.